Sharing Sustainability: How Values and Ethics Matter in Consumers’ Adoption of Public Bicycle-Sharing Scheme - Yin, Juelin (Journal of business ethics, 2018)
This study investigates the antecedents and mechanisms of consumers’ adoption of a public bicycle-sharing scheme (PBSS) as a form of shared sustainable consumption. Drawing on marketing ethics and sustainability literature, it argues that cultural and consumption values drive or deter the adoption of PBSS through the mediating mechanism of ethical evaluation. This study tests its hypotheses using a sample of 755 consumers from one of the largest PBSS programs in China. The results confirm the significance of collectivism, man–nature orientation, materialism, and face-consciousness as key determinants of the adoption of PBSS. Interestingly, these values play mixed roles in influencing PBSS adoption. It also finds that such values and beliefs need to be effectively translated into ethical evaluations of PBSS adoption, and need to be addressed in the specific social context. Thus, ethical evaluation constitutes a cognitive strategy that allows consumers to justify and defend their adoption of sustainability practices. The results suggest that a desirable sustainability program needs to not only cater to the cultural and psychological motivations of consumers, but also reflect the social norms and social context in which the sustainability practices and consumers are embedded.